Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Efektivitas Kerja Guru DI SMK Hidayatul Islam Clarak Kecamatan Leces Kabupaten Probolinggo - Agustina Pujiastuti; Tumini Tumini; Ahmad Hamdi (Ecobuss, 2016)
This research was conducted to find out the influence of leadership style and work discipline of effective working light of teachers in SMK Hidayatul Islam Clarak Leces District Probolinggo District. The population in this study were teachers and employees at SMK Hidayatul Islam Clarak Leces District Probolinggo district that requires 18 people. The sample used in this study is the entire population. The independent variables are leadership style (X1) and work discipline (X2) while the dependent variable is work effectiveness (Y). Data method used is interview, observation, documentation, literature study, questionnaire. Type of research used is. Result of research obtained 1) Equation Y = 8,337 + 0,559X1 + 0,147X2. 2) Result of calculation result of determination (R Square) equal to 0,385. This is expressed by the variable X (leadership style and work discipline) to the variation (up and down) variable Y (work effectiveness) of 38.5%, while the remaining 61.5% comes from factors other than leadership style And discipline work. 3) F test results showed 4.689 with a significance level of 0.026. Thus F-count = 4.689> F-table = 3.682, then H0 is rejected and Ha accepted. This shows the difference of leadership style and work discipline that have an effect and significant simultaneously on the effective work of teachers in SMK Hidayatul Islam Clarak Leces District Probolinggo District. 4) The value of t arithmetic X1 = 2.952> t-table = 2.131, then rejected and Ha accepted, there is a significant influence between leadership style on work effectiveness. The value of t arithmetic X2 = 0.829 <t-table = 2.131, then Ha rejected and H0 accepted, there is no partially significant influence between work discipline on work effectiveness. 5) The value of t arithmetic X1 = 2.952> The value of t arithmetic X2 = 0.829, leadership style (X1) has the dominant influence (the greatest) to effective work (Y) in SMK Hidayatul Islam Clarak Leces District Probolinggo. Keywords: leadership style, work discipline, work efficiency.